Out of context, beyond the face : neuroanatomical pathways of emotional face-body language integration in adolescent offenders (2019)
Background: Adolescent offenders (AOs) are characterized by social-norm transgression and aggressive behaviors. Those traits have been associated with alterations in socio-cognitive processes, including facial emotion recognition. While this would suggest